Employee filing band saw at Cliffs Dow plant in Marquette, Michigan - Dow Chemical Company (1949)
General view of an unidentified employee filing a band saw in the sawmill at the Cliffs Dow wood distillation plant located in Marquette, Michigan. Seeking a source of raw material for its new plastic, ethylcellulose, the Dow Chemical Company joined with the Cleveland-Cliffs Iron Company to form the Cliffs Dow Chemical Company in April 1935. The Cliffs Dow plant in Marquette primarily produced charcoal used in the manufacture of pig iron, as well as a range of chemical by-products including acetic acid, calcium acetate, wood alcohol, and ethyl alcohol. Notably, when the Marquette plant ceased operations in 1969, it was the last wood distillation plant in the United States.
Keywords: Wood distillation; Employees; Band saws; Dow Chemical Company; Chemical industry--By-products; Cleveland-Cliffs Iron Company; Sawmills; Machinery; Sawmill workers; Sawmills--Equipment and supplies